Исследование линейных импульсных электромеханических преобразователей комбинированного типа - Болюх, Владимир Федорович; Кочерга, Александр Иванович; Месенко, Александр Петрович; Щукин, Игорь Сергеевич (Одеський національний політехнічний університет, 2018)
Установлены особенности протекания электромагнитных процессов и определены электрические, магнитные и силовые показатели линейных импульсных электромеханических преобразователей комбинированного типа, включающих катушечный, ферромагнитный и один или два электропроводящий якоря. Выполнен сравнительный анализ различных преобразователей комбинированного типа с использованием критерия эффективности, который в относительном виде учитывает электрические, силовые и полевые показатели.

A mathematical model of a linear pulsed electromechanical converter (LPEC) of a combined type is developed, including the anchors of inductive, electrodynamic and electromagnetic type converters. A two-dimensional mathematical model with spatially-distributed parameters and corresponding boundary conditions is used. The mathematical model describes the interrelated electromagnetic, thermal and mechanical processes that occur when the inductor is excited from a capacitive energy storage device. The computer model of LPEC is realized in the software package Comsol Multiphysics. In the presence of two electrically conductive anchors, they are located on opposite sides of the inductor, so that with the help of movable clamps provide additional power action on the object. The ferromagnetic anchor is located on the side of the inductor opposite to the direction of the force action on the object. The features of the course of electromagnetic processes are determined and the main electric, magnetic and power indices of a number of LPECs of a combined type, including a coil, ferromagnetic and one or two electrically conductive anchors are determined. It is established that the inductor current varies in time in the form of an aperiodic polar pulse, while the current in the electrically conducting armature changes polarity after a while. This affects the nature of the electrodynamics forces. The maximum current density along the section of the electrically conductive armature takes place in its middle part, facing the inductor. The maximum induction of the magnetic field occurs in the middle of the gap between the inductor and the armature. A comparative analysis of various LPECs of a combined type was carried out using the efficiency criterion, which takes into account the electric, force and field (induction of the magnetic scattering field) indices in a relative form. Several variants of the strategy for assessing the effectiveness of the LPEC have been used, in which the priority of the corresponding indicator is estimated by the dimensionless weighting factor. It is established that practically all converters of combined type have a higher efficiency in comparison with LPEC of induction type, which is accepted as a basic variant. The most effective is LPEC with two electrically conductive anchors and a coil anchor, which is connected in series with the inductor. This converter with different variants of the estimation strategy is 3-5 and more times more efficient than the LPEC of induction type.
Investigation of linear pulse electromechanical converters of combined type
Keywords: электромеханические преобразователи; преобразователи комбинированного типа; математическая модель; электропроводящий якорь; катушечный якорь; ферромагнитный якорь; electromechanical converter; mathematical model; electrically conductive anchor; coil anchor; ferromagnetic anchor